Enhanced interfacial solar steam generation with composite reduced graphene oxide membrane. (December 2019) - Cheng, Gong; Wang, Xinzhi; Liu, Xing; He, Yurong; Balakin, Boris V.
Graphical abstract: Highlights: A simple composite enhanced system (CES) was proposed for solar steam generation. Highly efficient solar steam generation could be realized under 1 sun irradiation. The rGO can enhance the capillary transport of the filter paper. The CES can improve steam generation efficiency obviously compare to the membrane. Abstract: Solar steam generation, as a high efficiency photo-thermal conversion method, has enormous potential for many industrial applications. In this work, a reduced graphene oxide (rGO) composite membrane with high light absorption was prepared to enhance the steam generation of water successfully. Through different experimental tests, the evaporation rate and efficiency reached 0.9 kg·h −1 ·m −2 and 45.1% at 1 sun, even with a small amount of rGO (0.76 g/m 2 ). Furthermore, a simple composite enhanced system (CES) based on the rGO composite membrane was fabricated to further improve the evaporation efficiency. The evaporation rate and efficiency reached 1.37 kg·h −1 ·m −2 and 85.6% at 1 sun when the same amount of rGO was used in our novel CES. This was due to the decrease in the thermal conductivity and capillary enhancement of the supply water. Comparing the different methods of steam generation, it was observed that the evaporation efficiency of CES was higher than that of other systems, due to the decreased thermal loss. Finally, an integrated distillation and power generation device was assembled to demonstrate the practical application of CES and it exhibited great performance. It was of great significance for large-scale steam generation in distillation, sewage treatment, and other applications.